2016
DOI: 10.17795/jjhs-34239
|View full text |Cite
|
Sign up to set email alerts
|

Functional, Structural and Non-Structural Preparedness of Ahvaz Health Centers Against Disasters in 2014 – 2015

Abstract: Background: Entrance of heavy metals into the respiratory system has adverse effects on human health. Accordingly, measuring metals concentration in places and times is necessary. Objectives: This study was done to evaluate the non-carcinogenic risk of Pb, Cd, and As in air suspended particles of Baharestan city, in Isfahan, during 2016 -2017. Methods: In order to evaluate the non-carcinogenic risk of heavy metals in air suspended particles (PM10), sampling was performed using a SKC pump with a low volume (1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
2
4
1
Order By: Relevance
“…In this study, the average safety score of the assessed healthcare facilities was approximately 30 out of 100. Although this nding correspond with the average safety score of 16078 healthcare centers that measured in Iran, 2015 [19], but it is lower than the obtained safety score of PHC centers in the study in Ahwaz [20] and also, the hospitals across the country [21].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In this study, the average safety score of the assessed healthcare facilities was approximately 30 out of 100. Although this nding correspond with the average safety score of 16078 healthcare centers that measured in Iran, 2015 [19], but it is lower than the obtained safety score of PHC centers in the study in Ahwaz [20] and also, the hospitals across the country [21].…”
Section: Discussioncontrasting
confidence: 74%
“…The average score of structural safety in this assessment did not achieve an acceptable score, and it was even lower than the structural safety rate of hospitals in Iran [21]. This result con rms the ndings of the study conducted by Ardalan et al about the vulnerability of health facilities with focus on incomprehensive rural health centers at time of disasters [9].…”
Section: Discussionsupporting
confidence: 67%
“…In this study, the average safety score of the assessed PHC facilities was approximately 30 out of 100. Although this nding is in line with the average safety score of 16078 PHC centers that measured in Iran, 2015 [30], but it is lower than the obtained safety score of PHC centers in the study in Ahwaz [31]. A few international studies found that they have assessed the safety of health facilities using the same tool used in this study.…”
Section: Discussionsupporting
confidence: 72%
“…The functional preparedness of PHC facilities in this study was not acceptable and was low in comparison to the functional preparedness of PHC facilities in Ahwaz study [31]. Moreover, although the functional preparedness of PHC facilities under assessment achieved the lowest score (16.5) in this study but it was higher than the assessed rate across the Iran country (11.9) [30].…”
Section: Discussionmentioning
confidence: 65%
“…In this study, the average safety score of the assessed PHC facilities was approximately 30 out of 100. Although this nding correspond with the average safety score of 16078 PHC centers that measured in Iran, 2015 [28], but it is lower than the obtained safety score of PHC centers in the study in Ahwaz [29] and also, the hospitals across the country [19]. A few studies found that they have assessed the preparedness of health care facilities or hospitals using the same tool used in this study in other countries.…”
Section: Discussionmentioning
confidence: 48%